A comparative review of myocarditis in pediatrics versus adults: pathogenesis, diagnosis, and management - Ricci, Jacob C.; Farahani, Nick A.; Davis, Cormac J.; Ritter, Kyra G.; Parrow, Lauren M.; Tomerlin, Priya I.; Darakjian, Ashley A.; Gegoutchadze, Katherine; Gupta, Dipankar; Bruno, Katelyn A. (Frontiers in Immunology, 2025)
Myocarditis is an inflammatory heart disease that is more prevalent in men. The etiology of myocarditis is often multifactorial with viral infections being a predominant cause of myocarditis. Other etiologies such as autoimmune mediated or secondary to certain medical therapies such as immune checkpoint inhibitors are also seen however less commonly. The wide spectrum of clinical symptoms with which these patients present and the lack of reliable patterns or biomarkers of progression make it difficult to both diagnose and risk-stratify patients. Importantly, this disease is widely prevalent in pediatric populations and is a leading cause of sudden cardiac death in young patients. However, much of the knowledge of pathogenesis and treatment of this disease is extrapolated from adult studies. Current research in myocarditis has increasingly identified the role of hormones and the apparent sex differences seen predominantly in adult patients; however, such data is not well established in pediatric patients. Thus, there is an increased need to evaluate the age and sex-based differences in pediatric patients with myocarditis. Therefore, this review aims to present an overview of our current understanding of pathogenesis, diagnosis, and treatment strategies for myocarditis, with an emphasis on outlining both adult and pediatric studies to emphasize the continued need for research into this disease.